2002
DOI: 10.1097/00003246-200205000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epinephrine and vasopressin in a piglet model of prolonged ventricular fibrillation and cardiopulmonary resuscitation*

Abstract: In this pediatric porcine model of ventricular fibrillation, the combination of epinephrine with vasopressin during cardiopulmonary resuscitation resulted in significantly higher levels of left ventricular myocardial blood flow than either vasopressin alone or epinephrine alone. Both vasopressin alone and the combination of epinephrine with vasopressin, but not epinephrine alone, improved total cerebral blood flow during cardiopulmonary resuscitation. In stark contrast to asphyxial cardiac arrest, vasopressin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…These results are consistent with our observation that cardiac contractility is diminished in hearts of animals with HF and elevated plasma AVP. By contrast, AVP has been shown to improve survival in swine after experimental cardiac arrest, presumably due to enhanced myocardial blood flow secondary to enhanced peripheral vasoconstriction 49-53 . Unfortunately, AVP has not consistently proven beneficial in humans in large clinical trials of patients who have sustained cardiogenic shock 54-57 .…”
Section: Discussionmentioning
confidence: 96%
“…These results are consistent with our observation that cardiac contractility is diminished in hearts of animals with HF and elevated plasma AVP. By contrast, AVP has been shown to improve survival in swine after experimental cardiac arrest, presumably due to enhanced myocardial blood flow secondary to enhanced peripheral vasoconstriction 49-53 . Unfortunately, AVP has not consistently proven beneficial in humans in large clinical trials of patients who have sustained cardiogenic shock 54-57 .…”
Section: Discussionmentioning
confidence: 96%
“…They found that coronary perfusion pressure, left ventricular myocardial blood flow, and ROSC rates were higher in the 45 and 90 mcg/kg groups compared to the two lower dose groups. Further studies established that the combination of epinephrine and vasopressin was superior in the swine model of ventricular fibrillation, 41, 42 pulseless electrical activity, 43 asphyxial cardiac arrest 4446 and recently in the swine model of bupivacaine-induced cardiac arrest. 9 …”
Section: Discussionmentioning
confidence: 99%
“…The latter observation may relate to redistribution in blood flow or an indirect effect of vasopressin on cerebral blood flow, although these observations are speculative. In a pediatric (porcine) model of VF arrest, vasopressin, alone or in combination with HDE, significantly improved total cerebral blood flow during CPR (28). The authors speculate that improvements in brain perfusion may relate to vasopressin-mediated nitric oxide release and cerebral vasodilation.…”
Section: Impact Of Vasopressin On Myocardial Performancementioning
confidence: 93%